Editorial Note Vol.1 - Chand, Hari Prakash (Asian Journal of International Affairs, 2021)
At this moment where Nepal has surfaced as a sensitive geopolitical center for global powers, the Kathmandu School of Law (KSL), a reputed law college in Nepal, is proud to bring Nepal's first comprehensive Journal focusing on Asian Affairs in the international arena. It comprises six major parts entitled 'Editorial Note', 'Research Articles', 'Essay', 'Advisor's Opinion', 'Book Review', and 'AJIA Dialogue'. [for more see full text]